1988
DOI: 10.1038/bjc.1988.14
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tumour growth on liver pantothenate, CoA, and fatty acid synthetase activity in the mouse

Abstract: Summary Enzymatic, and microbiological assays were used to determine the hepatic contents of coenzyme A, acetyl CoA, fatty acid synthetase activity, and pantothenate in livers of tumour-bearing mice. Significant decreases in CoA and acetyl CoA were found in mice bearing (Balducci & Hardy, 1985;Shapot & Blinov, 1974). Some specific changes however are seen in malnourished animals, but not in those with experimental cancer, and recently we showed that in tumour-bearing mice, the hepatic content of acetyl coen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…These overlapping hits included both siRNA targeting CHK1 as well as both siRNA targeting ATR. Several other interesting candidate genes were also identified such as CAMK1, STK6, PANK2 and EPHB1, all of which have been previously reported as being involved in cancer (Figure 1D ) [ 22 - 25 ].…”
Section: Resultsmentioning
confidence: 89%
“…These overlapping hits included both siRNA targeting CHK1 as well as both siRNA targeting ATR. Several other interesting candidate genes were also identified such as CAMK1, STK6, PANK2 and EPHB1, all of which have been previously reported as being involved in cancer (Figure 1D ) [ 22 - 25 ].…”
Section: Resultsmentioning
confidence: 89%
“…These include synthesis and oxidation of fatty acids, the Krebs cycle, ketogenesis, biosynthesis of cholesterol and acetylcholine, degradation of amino acids, regulation of gene expression and cellular metabolism via protein acetylation and others ( Figure 2 ) [ 1 , 22 , 23 ]. Abnormal biosynthesis and homeostasis of CoA and its derivatives are associated with various human pathologies, including diabetes, Reye's syndrome, cancer, vitamin B12 deficiency and cardiac hypertrophy [ 24 26 ]. Genetic studies in human and animal models revealed the importance of the CoA biosynthetic pathway for the development and functioning of the nervous system [ 27 , 28 ].…”
Section: Cellular Functions Of Coa and Its Thioester Derivativesmentioning
confidence: 99%
“…It has been shown that insulin, glucose, fatty acids, pyruvate, and ketone bodies inhibit CoA biosynthesis, while glucocorticoids and glucagon, as well as drugs such as clofibrate, increase tissue concentration of CoA (8 -12). Altered homeostasis of CoA has been observed in diverse disease states, such as diabetes, starvation, alcoholism, Reye syndrome, mediumchain acyl CoA dehydrogenase deficiency, vitamin B 12 deficiency, hypertension, and certain types of tumors (13)(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%